A Compact Triple Band Antenna for Military Satellite Communication, Radar and Fifth Generation Applications - El Hadri, D.; Zugari, A.; Zakriti, A.; El Ouahabi, M.; Taouzari, M. (Advanced Electromagnetics, 2020)
A compact triple band antenna by using etching slots technique in the radiation element is presented in this paper. The proposed antenna is designed to target three different frequencies: 7.5 GHz (military satellite communication), 9 GHz (radar applications) and 28 GHz (fifth generation applications). The fabricated prototype of the antenna has overall dimensions of 13x12.8x1.6 mm3. Measurements were carried out to validate the simulation results. The impedance bandwidths are 259 MHz (7.435-7.695 MHz), 355 MHz (8.86-9.221 MHz) and 2.67 GHz (26.79-29.433 GHz) with return loss less than -10 dB. Furthermore, the suggested antenna provides a gain of 3.96 dBi, 3.05 dBi and 5.86 dBi at 7.5 GHz, 9 GHz and 28 GHz respectively. Therefore, the results demonstrate that the proposed triple band antenna can be used for military satellite communication, radar applications and is a good candidate for the future 5G applications.